1999
DOI: 10.1046/j.1440-1827.1999.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pepsinogen II with androgen and estrogen receptors in human prostate carcinoma

Abstract: The expression of pepsinogen II (PG II), an aspartyl proteinase usually involved in the digestion of proteins in the stomach, was immunohistochemically investigated in conjunction with androgen (AR) and estrogen receptor (ER) status in prostate adenocarcinomas. Of a total of 38 samples obtained from radical prostatectomies, 23 tumors (60.5%) were positive for PG II and there was a significant positive correlation to the expression of AR but not to ER. Cells positive for PG II were localized mainly to the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Similarly, PGC activity in the four autopsy prostates was observed almost entirely within the central zone and ended abruptly at the boundary between the peripheral and central zones. This condition appears to be altered in abnormal glands, with the observation of PGC expression by peripheral zone tumors (17). In our study, using the qRT-PCR technology, we detected PGC expression even in the peripheral zones of prostates without carcinoma.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, PGC activity in the four autopsy prostates was observed almost entirely within the central zone and ended abruptly at the boundary between the peripheral and central zones. This condition appears to be altered in abnormal glands, with the observation of PGC expression by peripheral zone tumors (17). In our study, using the qRT-PCR technology, we detected PGC expression even in the peripheral zones of prostates without carcinoma.…”
Section: Discussionsupporting
confidence: 57%
“…British Journal of Cancer (2004) 1993;Miettinen et al, 1995;Vizoso et al, 1995;Konishi et al, 1999;Venturini et al, 1999;Berns et al, 2000;Miyasaka et al, 2001;Saito et al, 2002). In the present study, the expression of these genes did not increase in either group 2, the larger adenomas or group 3, the adenocarcinomas.…”
Section: Discussionsupporting
confidence: 38%
“…The overexpression of PGC has also been determined in the cancerous cells, basal cell, and squamous cell carcinomas of the eyelids (Alvarez et al, 2004). Similarly, extra-digestive expression of PGC has been reported in several tumors such as cervical, endometrial and ovarian (Serra Diaz et al, 1999), prostate (Konishi et al, 1999), gastric , stomach (Tatematsu et al, 1990), gall bladder (Tatematsu et al, 1988), breast carcinomas (Serra Diaz et al, 1999), and cutaneous malignant melanomas (Quintela et al, 2001). Interestingly, these expressions are significantly associated with a longer overall survival of patients with breast carcinomas .…”
Section: Role Of Pgc In the Tumor Progressionmentioning
confidence: 90%
“…PGC expression level has also been reported in gastric epithelial cells (Fukuda et al, 1994), stomach (Tatematsu et al, 1990), pancreas (Fukushima et al, 2004), liver (Steele et al, 2007), prostate (Konishi et al, 1999), and Barrett epithelium (Pals et al, 1988). However, Bobe and Goetz (2001) have shown that PGC is also present in the animal ovary.…”
Section: Site Of Expressionmentioning
confidence: 92%
See 1 more Smart Citation